PENGARUH KOMUNIKASI INTERPERSONAL GURU DAN DISIPLIN KERJA TERHADAP MOTIVASI SERTA DAMPAK PADA KINERJA GURU PADA GURU SMK THERESIANA SEMARANG (Jurnal Mahasiswa Pasca Sarjana, 2013)
The purpose of this research is to examine and analyze the influences communication interpersonal teacher, work discipline, the importance work motivation have a role as mediator variabel to communication interpersonal teacher and work discipline for increasing of teacher’s job performance in SMK Theresiana Semarang.The population in this research are 90 civil servant teachers in SMK Theresiana Semarang that used for the research as respondents.The methodologies of data collection use questionnaires with Likert scale in the range 1 – 7, and are used as primary data or data got from questionnair’s answer respondents. Statistical technique used was multiple regression analysis.The results show that communication interpersonal teacher, work discipline, and work motivation communication among teacher and work discipline can explain variations in performance of teachers SMK Theresiana Semarang by 76.4 %, the rest explained by other factors not examined in this research. The work discipline have influenced is more dominant by 23.6% than the communication interpersonal teacher for increasing of teacher’s job performance, but work motivation can to mediation communication interpersonal teacher and work discipline for increasing of teacher’s job performance in SMK Theresiana Semarang. Key word : Communication interpersonal teacher, work discipline, work motivation, and teacher’s job performance.